International good practices on central venous catheters' placement and daily management in adults and on educational interventions addressed to healthcare professionals or awake/outpatients. Results of a scoping review compared with the existent Italian good practices - Mastrandrea, Giovanni; Giuliani, Rachele; Graps, Elisabetta A. (Frontiers in Medicine, 2022)
This scoping review aims to check the existing international literature related to the placement and management of Central Venous Catheters (CVCs) in adults and compare them with the Good Practices published by the Italian Society of anesthesiology intensive care (hereafter “SIAARTI Good Practices”) and the protocols written by the Italian Expert group on Long Term Central Venous Accesses (hereafter “GAVeCeLT Protocols”) and verify the existence of experiences focused on the daily assessment of the implantation site and on educational interventions on awake patients or caregivers to enhance their empowerment. A systematic search approach has been applied. Our composite research question has been primarily defined by the PICO: only patients over 18 years of age with CVC for any clinical reason except for kidney replacement therapy; placement and management of CVCs with procedures recommended by the recent international Guidelines/Bundles and specific educational interventions are the interventions to be compared with standard CVC placement and management without any educational interventions. Two different types of outcomes have been taken into consideration: Catheter-Related Complications Rate (A) and Patient/Caregiver Involvement (B). Eligible articles have been limited to Systematic Review OR Methanalisys OR Guidelines in Human field, focusing on adults, English language only, from Jan 2015 to Dec 2020. Searched Medical Subject Headings (MeSHs) Terms were “venous” AND “catheters” and the correspondence with the designed PICO framework was then checked directly by the authors. A comprehensive search was conducted by two reviewers on 15 February 2021 in four databases and 32 full-text articles were finally included and qualitatively assessed. The included articles appear to be in line with the indications provided by the available Italian Good Practices and explain the complexity of this procedure. The need to promote the use of bundles and checklists related to CVC placement and dressing procedures comes to light. These organizational technologies can be implemented following the creation of teams dedicated to venous access that are subjected to continuous training. As regards the impact of educational initiatives, implementing paths of health education and proper hospital discharge preparation for both healthcare workers and families increases safety for the patient with CVC.